2018
DOI: 10.1159/000492644
|View full text |Cite
|
Sign up to set email alerts
|

Overexpressed D2 Dopamine Receptor Inhibits Non-Small Cell Lung Cancer Progression through Inhibiting NF-κB Signaling Pathway

Abstract: Background/Aims: Non-small cell lung cancer (NSCLC) is one of the deadliest cancers worldwide. Dopamine receptor D2 (DRD2) has multiple roles in clinical progression of NSCLC and functional maintenance of cancer cells. However, little is known about the molecular mechanism. Here, we clarified whether DRD2 inhibits lung cancer progression and identified the underlying downstream signaling. Methods: DRD2 mRNA and protein levels were detected in clinical specimens by qRT-PCR and immunohistochemistry, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Overexpression of D2 receptors was found to inhibit growth in non-small cell lung cancer cell lines [34], and D2-receptor agonists abrogated lung tumor progression in human xenograft murine models [35].…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Overexpression of D2 receptors was found to inhibit growth in non-small cell lung cancer cell lines [34], and D2-receptor agonists abrogated lung tumor progression in human xenograft murine models [35].…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…43 Blocking the NF-kB pathway can alleviate and even prevent disease development and deterioration. 44,45 miR-149* has anti-inflammatory properties in vitro and in vivo. 13 The present results reveal that miR-149* prevents the phosphorylation of IkBa and NF-kB transactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of NF-ĸB signaling pathway promotes PCa progression and significantly correlates with advanced diseases (72). It has been shown that DRD2 activation suppresses nuclear translocation of NF-ĸB in the intracerebral hemorrhage mouse model, and DRD2 depletion retards non-small cell lung cancer progression through the inhibition of NF-ĸB (54,55). NF-ĸB transcriptionally activates the expression of multiple oncogenic factors, including anti-apoptotic proteins survivin and Mcl-1 (73,74).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of DHECS on other putative dopamine receptor-mediated signaling pathways was also investigated (53)(54)(55). DHECS reduced the phosphorylation of calcium/calmodulin-dependent protein kinase kinase 2 (CaMKK2) at Ser511 and increased the phosphorylation of 5'-AMP-activated protein kinase (AMPK) at Thr172 in a time-dependent manner ( Figure 4A), indicating that DHECS may also activate AMPK and augment its function as a tumor suppressor in chemoresistant PCa cells.…”
Section: Dhecs Affects the Expression And Downstream Signaling Of Dopmentioning
confidence: 99%